A new passive immune strategy based on IgY antibodies as a key element to control neonatal calf diarrhea in dairy farms - Vega, Celina Guadalupe; Bok, Marina; Ebinger, Maren; Rocha, Lucía Alejandra; Rivolta, Alejandra Antonella; González Thomas, Valeria; Muntadas, Pilar; D’Aloia, Ricardo; Pinto, Verónica; Parreño, Viviana; Wigdorovitz, Andres (BMC, 2020)
Background: Neonatal diarrhea remains one of the main causes of morbi-mortality in dairy calves under artificial rearing. It is often caused by infectious agents of viral, bacterial, or parasitic origin. Cows vaccination and colostrum intake by calves during the first 6 h of life are critical strategies to prevent severe diarrhea but these are still insufficient. Here we report the field evaluation of a product based on IgY antibodies against group A rotavirus (RVA), coronavirus (CoV), enterotoxigenic Escherichia coli, and Salmonella sp. This product, named IgY DNT, has been designed as a complementary passive immunization strategy to prevent neonatal calf diarrhea. The quality of the product depends on the titers of specific IgY antibodies to each antigen evaluated by ELISA. In the case of the viral antigens, ELISA antibody (Ab) titers are correlated with protection against infection in calves experimentally challenged with RVA and CoV (Bok M, et al., Passive immunity to control bovine coronavirus diarrhea in a dairy herd in Argentina, 2017), (Vega C, et al., Vet Immunol Immunopathol, 142:156–69, 2011), (Vega C, et al., Res Vet Sci, 103:1–10, 2015). To evaluate the efficiency in dairy farms, thirty newborn Holstein calves were randomly assigned to IgY DNT or control groups and treatment initiated after colostrum intake and gut closure. Calves in the IgY DNT group received 20 g of the oral passive treatment in 2 L of milk twice a day during the first 2 weeks of life. Animals were followed until 3 weeks of age and diarrhea due to natural exposure to infectious agents was recorded during all the experimental time. Results: Results demonstrate that the oral administration of IgY DNT during the first 2 weeks of life to newborn calves caused a delay in diarrhea onset and significantly reduced its severity and duration compared with untreated calves. Animals treated with IgY DNT showed a trend towards a delay in RVA infection with significantly shorter duration and virus shedding compared to control calves. Conclusions: This indicates that IgY DNT is an effective product to complement current preventive strategies against neonatal calf diarrhea in dairy farms. Furthermore, to our knowledge, this is the only biological product available for the prevention of virus-associated neonatal calf diarrhea.